PORTRAIT OF PESANTREN TEACHERS: EXAMINING PROFESSIONALISM BEHIND THEIR VARIOUS EDUCATIONAL QUALIFICATIONS - Sanjaya, Ni’mal Maula; Amani, Hanin Wahidatul; Putra, Raja; Sholichati, Dhuhuri; Jannah, Mutiara; Zahroh, Lathifah Az; Rahmawati, Susi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Teacher professionalism in Islamic boarding schools (pesantren) plays a crucial role in maintaining the quality of Islamic education amid the dynamics of globalization and national regulatory demands regarding teacher qualification standards. This study aims to examine the professionalism of pesantren teachers by analyzing the diversity of their educational backgrounds and its influence on teaching practices and institutional quality. The research employed a descriptive qualitative approach. Data were collected through semi-structured interviews, field observations, and document analysis. Informants were selected purposively based on the criteria of having at least two years of teaching experience and diverse educational backgrounds. The findings reveal that variations in educational qualifications influence the characteristics of teacher professionalism in pesantren. Teachers with formal teacher education backgrounds tend to demonstrate more systematic lesson planning and classroom management skills. In contrast, teachers from non-teaching educational backgrounds are more prominent in providing spiritual role modeling and character development for students. These two characteristics complement each other in supporting the quality of education in pesantren. This study concludes that strengthening teacher professionalism in Islamic boarding schools requires the integration of modern pedagogical competencies with the spiritual values that characterize pesantren education. Therefore, teacher capacity development should be promoted through continuous training programs, professional learning communities, and internal mentoring systems that maintain a balance between educational innovation and the preservation of pesantren traditions. ABSTRAK Profesionalisme guru di lingkungan pesantren menjadi faktor penting dalam menjaga mutu pendidikan Islam di tengah dinamika globalisasi dan tuntutan regulasi nasional terkait standar kualifikasi pendidik. Penelitian ini bertujuan untuk mengkaji profesionalisme guru pesantren dengan menelaah keberagaman latar belakang pendidikan serta pengaruhnya terhadap praktik pembelajaran dan kualitas kelembagaan. Penelitian menggunakan pendekatan kualitatif deskriptif. Data dikumpulkan melalui wawancara semi-terstruktur, observasi lapangan, dan studi dokumentasi. Informan dipilih secara purposive dengan kriteria guru yang memiliki pengalaman mengajar minimal dua tahun serta latar belakang pendidikan yang beragam. Hasil penelitian menunjukkan bahwa variasi kualifikasi pendidikan memengaruhi karakter profesionalisme guru pesantren. Guru dengan latar belakang pendidikan keguruan cenderung memiliki kemampuan perencanaan dan pengelolaan pembelajaran yang lebih sistematis. Sementara itu, guru dengan latar belakang non-keguruan lebih menonjol dalam keteladanan spiritual dan pembinaan karakter santri. Kedua karakteristik tersebut saling melengkapi dalam mendukung kualitas pendidikan pesantren. Penelitian ini menyimpulkan bahwa penguatan profesionalisme guru pesantren memerlukan integrasi antara kompetensi pedagogik modern dan nilai-nilai spiritual yang menjadi ciri khas pendidikan pesantren. Oleh karena itu, pengembangan kapasitas guru perlu dilakukan melalui pelatihan berkelanjutan, komunitas belajar profesional, serta sistem mentoring internal yang mampu menjaga keseimbangan antara inovasi pendidikan dan pelestarian tradisi pesantren.